Analisis Stabilitas Lereng dengan Metode Bishop pada Proyek Geotechnical Investigation Jalur Transportasi Pelabuhan Batubara Marangkayu Kabupaten Kutai Kartanegara - Yonas Prima Arga Rumbyarso; Gali Pribadi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
A slope is a surface that has a slope and forms a certain angle to the horizontal plane and is not protected. The slope and angle formed cause the slopes to have differences in surface height. Differences in slope surface height result in forces acting to push, and also forces in the soil acting to resist or resist, so that the position of the soil remains stable. The stability of a slope is expressed in the slope safety factor which is obtained or obtained by comparing the holding force and the pushing force. Based on topographic data of ground investigation drilling points on the Marangkayu Coal Port transportation route, Kutai Kartanegara Regency, it is known that there are several drilling points with soil conditions in the form of slopes or hills, so it is predicted that they could cause the potential for landslides because these points will become transportation routes for loading and unloading materials. coal. The aim of this research is to determine the slope safety figures, and to obtain a safe slope with the original slope conditions. The method used to analyze slope stability in this research uses Geostudio Slope Bishop method software. The results of the analysis of the original slope conditions at the OLC-FBH-03 and OLC-FBH-06 test points showed that the slope safety value was obtained with the result being that the slope condition was safe from landslides (FK>1.25). With this, it can be concluded that the Marangkayu Coal Harbor transportation route, Kutai Kartanegara Regency is safe from landslides.Keywords: Bishop Method, Geostudio Slope, Slope Stability, Slope Safety Value